A Bidirectional Generalized Synchronization Theorem -Based Chaotic Pseudorandom Number Generator - Han Shuangshuang; Min Lequan (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
In order to design good pseudorandom number generator, using a bidirectional generalized synchronization theorem for discrete chaos system, this paper introduces a new 5-dimensional bidirectional generalized chaos synchronization system (BGCSDS), whose prototype is a novel chaotic system. Numerical simulation showed that two pair variables of the BGCSDS achieve generalized chaos synchronization via a transform H. A chaos-based pseudorandom number generator (CPNG) was designed by the new BGCSDS. Using the FIPS-140-2 tests issued by the National Institute of Standard and Technology (NIST) verified the randomness of the 1000 binary number sequences generated via the CPNG and the RC4 algorithm respectively. The results showed all the tested sequences passed the FIPS-140-2 tests. The confidence interval analysis showed the statistical properties of the randomness of the sequences generated via the CPNG and the RC4 algorithm do not have significant differences. So, the CPNG is suitable to be used in the information security filed.